Comparative study on production performances of the Japanese, White, Black and Brown quail at fifth generation (Bangladesh Journal of Livestock Research, 2020)
Four quail genotypes namely Japanese (J), White (W), Black (Bl) and Brown (Br) quail are being maintaining at Bangladesh Livestock Research Institute to develop meat type quail genotype. Studied fifth generation (G5) quails were hatched from 4th generation (G4) parents based on estimated breeding value for 5th week body weight. Standard management practices were followed during study period. Hatching eggs were collected from every single pen of the selected parent quails. A total of 1750 day-old chick comprising of J, W, Br and Bl were hatched in one batch. Collected data were analyzed in a CRD by General Linear Model (GLM) Univariate Procedure in SPSS Computer Program. Body weight of quails at 3rd, 4th, and 6th week of age were (p